(untitled) (Research, Society and Development, 2024)
Objective: The objective of this narrative literature review article was to address the origin and history of Phytotherapy, some types of herbal medicines and their benefits within dentistry, addressing how the production of a herbal medicine occurs and what difficulties may exist within Phytotherapy. Methodology: Searches and research were carried out using descriptors, websites, newspapers and other databases, including: Research, society and development journal, Web of Science, DeCs, VHL/BIREME, Science Direct, PUBMED Central, The Cochrane Library, Scielo journals and gray literature. Results: We obtained the result that Phytoterpia has great utility and benefits within dentistry, positive points given its low market value and mainly due to its antibacterial, anti-inflammatory, antihemorrhagic, anesthetic and other functions.